MENDUGA POTENSI PRODUKSI KAYU BULAT DARI HUTAN KALIMANTAN TIMUR MENGGUNAKAN METODE PENDUGAAN NISBAH DAN PENDUGAAN REGRESI - Han Roliadi; Buharman Buharman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
For predicting the roundwood potential in the forest region of East Kalimantan, roughly two kinds of data are required. These includes sample data and population data. Sample data collected are the area or size of several selected forest region and the volume of the corresponding roundwood production, while population data include the total forest area of East Kalimantan.The prediction methods applied are ratio estimate and regression estimate. Using ratio estimate, the volume of roundwood production potential predicted was 8 093 575 cu.m (7 032 723 to 9 154 427 cu.m). On the other hand, with the application of regression estimate, the uolume of roundwood production potential was 8 505 603 cu.m. (7 889 057 to 9 122 149 cu.m.).Examination of the residuals indicated that assumption of normality of data was satisfied